(untitled) (Journal of Nepal Geological Society, 1996)
Granitic rocks in the Doda district of Jammu and Kashmir State, NW Himalaya are exposed at eight places. They are named as Dramman, Piparan, Kaplas, Khol Dedni, Chinta, Bhala, Kai Nala, and Nagin Dhar Granites. They occur in the form of irregular bodies of varying dimensions. These granites are mostly leucocratic, two-mica, porphyritic to aplitic, massive and highly jointed with crude foliation in some cases. The contact with the Older Metamorphics is sharp and thermal aureole is absent. These granites are monzo- to syeno-granitic in composition with peraluminous, S-type (equivalent to ilmenite series) and calc-alkaline affinity. These intrusive bodies are emplaced within the Older Metamorphics under tectonic influences at later stages of metamorphism. They have formed from highly evolved anatectic granites derived by partial melting of lower crustal material with diapiric situations. These processes had been operative at a temperature of 600-700°C at a depth of 20-30 km under 5 Kb Pressure. The emplacement of these granites is suggested to be due to transient dilation where the diapir is enhanced by sheeting mechanism.